2004
DOI: 10.4049/jimmunol.172.5.3189
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Infected Lymphocytes Regulate Fibronectin Synthesis by TGFβ1 Secretion

Abstract: Alterations in lymph node architecture occur with HIV infection and contribute to immunological derangements. We previously showed that matrix fibronectin stabilized HIV and increased HIV infection of PBL. We showed increased fibronectin deposition in lymph nodes of HIV-infected patients. However, we did not detect a difference in fibronectin synthesis between uninfected and infected PBL. Therefore, we hypothesized that interactions of HIV-infected cells with fibroblasts resulted in increased fibronectin depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
2
13
0
3
Order By: Relevance
“…Data shows that patients with HIV-infected lymphocytes have elevated levels of FN1 in the cells themselves; this correlation is supported by the idea that FN1 plays a critical role in stabilizing the HIV infection process (Pal and Schnapp, 2004). Although the quantity of blood cell proteins has been up regulated, the amount of FN1 will be downregulated in plasma to compensate for the increased cellular levels.…”
Section: Discussionsupporting
confidence: 57%
“…Data shows that patients with HIV-infected lymphocytes have elevated levels of FN1 in the cells themselves; this correlation is supported by the idea that FN1 plays a critical role in stabilizing the HIV infection process (Pal and Schnapp, 2004). Although the quantity of blood cell proteins has been up regulated, the amount of FN1 will be downregulated in plasma to compensate for the increased cellular levels.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, we found that overexpression of the dominant negative Smad3 in HK-2 cells inhibited the Leptospira santarosai serovar Shermani OMP-induced increase of type I and type IV collagens, suggesting that Smad3, a downstream mediator of TGF-␤1, plays a pivotal role in this process. Several studies have demonstrated that infection with microorganisms, including parasite, virus, and bacterium, leads to an increase of TGF-␤1 production in different cell types (35)(36)(37). However, it is not clear that these infections can activate the TGF-␤ downstream Smad signaling.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β, a cytokine known to be involved in Treg conversion, is increased in lymphatic tissues during SIV- and HIV-infection and appears to be generated by Treg present there [11, 76]. TGF-β-producing Treg may then educate DC to become tolerogenic through a phenomenon termed “infectious tolerance” [77, 78], thereby perpetuating a cycle of immune-suppression.…”
Section: Discussionmentioning
confidence: 99%